Development of Torque and Drag Calculation Software for Oil Well Planning–Part 1: 2D Aadnoy Method - Singgih Satrio Wibowo; Herman Yoseph Sutarto (Journal of Petroleum and Geothermal Technology, 2022)
With the increasing number of drilled ultra-extended reach wells and complex geometry wells, the drilling limitation caused by excessive torque and drag forces must be further investigated. The wellbore friction being a main limiting factor in extended reach well needs to be studied with the new developed models. The torque and drag software implement two methods: (1) 2D and 3D analytical model developed by Aadnøy (Aadnoy & Andersen, 1998; Aadnoy & Andersen, 2001; Aadnoy & Djurhuus, 2008; Aadnoy, et al., 2010; Aadnoy, 2010) and (2) Miska and Mitchel, for 2D wellbore (Mitchell, et al., 2011). This paper presents the theory and implementation of 2D Aadnoy method. Quite diverse wellbore trajectory and depth has been chosen for a better evaluation and comparison of the model with the measured data. In order to investigate the potential and limitation of the model, torque and drag analysis during the different operations such as tripping in, tripping out, rotating off bottom, combined up/down were investigated.